(untitled) (Педагогіка вищої та середньої школи, 2008)
This article describes the effective technologies using which influence on the heads of departments, teachers work and, as a result, on quality o f students training. It is considered the communication skill as one of a component of modern management technologies that is the basic at development or improvement of teachers’ professional work. The results of the communication skills development at the higher school teachers are shown.